Full-Model Electric Field Analysis of Flexible HVDC Converter Valve Hall with Fast Multipole Boundary Element Method - Yuxin SHI; Zezhong WANG; Jiucai ZHAO (Zhongguo dianli, 2021)
The flexible HVDC converter valve hall has numerous equipment, complex structures and enclosed environment with coexistence of multiple medium, which makes the full-model electric field intensity analysis of the valve hall difficult in model building, large in calculation scale, and poor in efficiency with traditional methods. The symmetry fast multipole curved boundary element method (SFMCBEM) has the advantages of fast calculation speed and less memory consumption, and is suitable for solving large-scale problems. Two different structures of a ±160 kV flexible HVDC converter valve hall were modeled respectively and the SFMCBEM was used to calculate their full-model electric field with the number of nodes in calculation reaching up to 1.33 million. The influences of valve tower shielding system structure, bridge electric connection mode and valve hall arrangement on the surface electric field of fittings were analyzed, and the distribution characteristics of electric field in the valve hall were understood, which can provide a reference for equipment layout. The proposed method provides an effective means for understanding the electric field distribution in the flexible HVDC converter valve hall, and is of great significance for equipment insulation coordination design.